Larutan ekstrak kulit durian (Durio zibethinus Murr) terhadap kematian larva nyamuk aedes aegypti - Hamdani Hamdani (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Durian plant (Durio zibethinus Murr) is one example of a plant that has the potential as a natural insecticide that is safe for the environment. But now the utilization has not been done to the maximum. Durian fruit is one of the typical fruits of Indonesia, durian skin extract (Durio zibethinus Murr) as a control of Aedes aegypti mosquitoes that durian skin extract obtained by distillation and tested with a concentration of 25% is effective to kill mosquitoes.Objective: To determine the comparison of the effectiveness of durian (Durio zibethinus Murr) skin doses against the mortality rate of Aedes aegypti larvae.Method: This research is an experimental design that is to find out the most effective dose of durian skin concentration (Durio zibethinus Murr) as a control material for Aedes aegypti larvae. The number of samples taken from this study were 500 Aedes aegypti larvae for 3 treatments which in one treatment were 150 Aedes aegypti larvae to be included each as many as 25 individuals. The study was conducted in July 2017 at the Health Polytechnic Campus of the Ministry of Health, Aceh, namely at the Laboratory of the Department of Environmental Health of the Polytechnic Ministry of Health, Aceh Lagang Village, Darul Imarah District, Aceh Besar. Data analysis using one-way ANOVA was used to determine differences in the effectiveness of durian skin doses on the mortality rate of Aedes aegypti larvae. By conducting tests using a single ANOVA formula and LSD table.Results: The results showed that the dose of durian extract 5% by150 ml on average 13 larvae died, the dose of 10% by 150 ml on average 16.6 larvae died, and the dose of durian extract 15% by 150 ml on average 19.3 while the control group did not occur. The average value of p-value obtained is 0.000 (p < 0.05), there is a difference in the effectiveness of durian extract which is signi ﬁ cant with a dose of 15% by 150 ml is the most effective dose to kill larvae with a p-value= 0.001 (p < 0.05).Conclusion: There is a difference in the effectiveness of durian extract from the three doses of 5% by 150 ml, 10% by 150 and 15% by 150 ml. Among the doses of durian extract with the most effective dose among the three is the dose of durian extract solution by 150ml durian extract. Keywords